![\\y=2x^2-x^4\\ y'=4x-4x^3\\ y'=4x(1-x^2)\\ y'=-4x(x^2-1)\\ y'=-4x(x-1)(x+1)\\ -4x(x-1)(x+1)=0\\ x=0 \vee x=1 \vee x=-1\\ \\y=2x^2-x^4\\ y'=4x-4x^3\\ y'=4x(1-x^2)\\ y'=-4x(x^2-1)\\ y'=-4x(x-1)(x+1)\\ -4x(x-1)(x+1)=0\\ x=0 \vee x=1 \vee x=-1\\](https://tex.z-dn.net/?f=%5C%5Cy%3D2x%5E2-x%5E4%5C%5C+y%27%3D4x-4x%5E3%5C%5C+y%27%3D4x%281-x%5E2%29%5C%5C+y%27%3D-4x%28x%5E2-1%29%5C%5C+y%27%3D-4x%28x-1%29%28x%2B1%29%5C%5C+-4x%28x-1%29%28x%2B1%29%3D0%5C%5C+x%3D0+%5Cvee+x%3D1+%5Cvee+x%3D-1%5C%5C+)
при x∈(-∞,-1) y'>0 ⇒ функция возрастает
при x∈(-1,0) y'<0 ⇒ функция убывает</p>
при x∈(0,1) y'>0 ⇒ функция возрастает
при x∈(1,∞) y'<0 ⇒ функция убывает</p>
![\\y=\frac{1}{4}x^4 -x^2+5\\ y'=x^3-2x\\ x^3-2x=0\\ x(x^2-2)=0\\ x=0 \vee x=-\sqrt2 \vee x=\sqrt 2 \\y=\frac{1}{4}x^4 -x^2+5\\ y'=x^3-2x\\ x^3-2x=0\\ x(x^2-2)=0\\ x=0 \vee x=-\sqrt2 \vee x=\sqrt 2](https://tex.z-dn.net/?f=%5C%5Cy%3D%5Cfrac%7B1%7D%7B4%7Dx%5E4+-x%5E2%2B5%5C%5C+y%27%3Dx%5E3-2x%5C%5C+x%5E3-2x%3D0%5C%5C+x%28x%5E2-2%29%3D0%5C%5C+x%3D0+%5Cvee+x%3D-%5Csqrt2+%5Cvee+x%3D%5Csqrt+2)
при x∈(-∞,-√2) y'<0 ⇒ функция убывает</p>
при x∈(-√2,0) y'>0 ⇒ функция возрастает
при x∈(0,√2) y'<0 ⇒ функция убывает</p>
при x∈(√2,∞) y'>0 ⇒ функция возрастает